Preparation method of polyimide compression material with chained filler distribution
By applying AC voltage to form a filler chain distribution, the problems of charge accumulation and mechanical properties of polyimide materials in space environment are solved, and the electrical and thermal conductivity performance improvements under low filler content are achieved. Improved mechanical properties.
Patent Information
- Application Number
- CN202411147577.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-21
AI Technical Summary
In space environment, polyimide insulating materials accumulate charge due to the deposition of high-energy charged particles, causing electrostatic discharge, affecting the safe operation of the spacecraft, and increasing filler doping to improve electric field uniformity will damage the mechanical properties of the material.
Using the preparation method of polyimide compression junction material with a chain distribution of filler, an electric field is formed by applying an AC voltage to the molten mixed powder, so that the pressure-sensitive filler particles are arranged in chains to form a conductive and thermally conductive network, and the filler content is reduced to the material. Effects of performance.
At lower filler content, excellent nonlinear conductivity and good thermal conductivity are obtained, while reducing the negative impact of filler on the overall performance of the material and improving the mechanical properties of the material.
Smart Images

Figure CN119161731A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of insulating materials, and in particular relates to a method for preparing a polyimide compression material with chain-type distribution of fillers. Background Art
[0002] Among many polymers, polyimide has extremely outstanding comprehensive properties, including excellent mechanical properties, dielectric properties, heat resistance and high insulation properties. It is known as "one of the most promising engineering plastics in the 21st century" and can be widely used in aerospace, electrical and electronics, machinery manufacturing, water conservancy and other industrial fields.
[0003] In the field of aerospace, the main energy source of current spacecraft is the solar energy obtained by the solar array mechanism (SADA), among which the drive slip ring is the core component for realizing power transmission in the solar array drive mechanism. Polyimide, as the insulating material on the slip ring, ensures the stable operation of the slip ring. However, the space environment is extremely complex. The atomic oxygen, solar electromagnetic radiation, and charged particles in space will affect the performance of insulating materials. Extreme high-energy charged particles will penetrate the aluminum shielding shell and enter the SADA, and finally deposit in insulating media such as polyimide. Since the polyimide insulating medium has a low electrical conductivity, the deposited electrons are difficult to discharge, and charge accumulation is formed inside the medium. The accumulated charge will form a local electric field distortion inside the spacecraft drive slip ring. When the electric field strength exceeds the discharge threshold of the insulating medium, it will cause electrostatic discharge, and even cause serious damage to the safe operation of the spacecraft.
[0004] Polyimide modified with varistor filler has nonlinear conductivity characteristics. Its conductivity increases with the increase of electric field, and it can effectively release the accumulated charge at the electric field distortion point, thereby playing a role in uniform electric field and improving electric field distortion. However, according to the actual application scenario, in order to effectively play a role in uniform electric field, it is often necessary to dope more varistor fillers. Relevant research by scholars has shown that an increase in the filler doping content often causes a deterioration in the mechanical properties of the material. Therefore, while ensuring the uniform field requirements, minimizing the filler content and improving the comprehensive performance of the insulating material are the directions for our further efforts. Summary of the invention
[0005] In view of the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing a polyimide compression material with a filler chain distribution. The specific technical scheme is as follows:
[0006] A method for preparing a polyimide compression material with a filler chain distribution comprises the following steps:
[0007] S1 raw material pretreatment: drying the pressure-sensitive filler and the polyimide molding powder, stirring and breaking up the pressure-sensitive filler, and then sieving the pressure-sensitive filler and the polyimide molding powder respectively;
[0008] S2 Mixing and sieving: After the pressure-sensitive filler and the polyimide molding powder are mixed evenly in a mixer, the mixed powder is sieved;
[0009] S3 mold sintering: the sieved mixed powder is loaded into a mold, and then placed in a sintering furnace to sinter the mixed powder into a molten state;
[0010] S4 field pressing: apply AC voltage to the upper and lower parts of the mold filled with molten mixed powder, then press and shape at constant pressure, cool to room temperature and demould to obtain a compressed material with chain distribution of fillers.
[0011] like Figure 1 This is a force analysis diagram of the varistor filler particles after voltage is applied, which shows the principle of chain arrangement of the varistor filler. The dielectric constant of the varistor filler is quite different from that of the polyimide matrix. Under AC voltage, the varistor filler particles, as dielectric particles, are polarized in the electric field and move under force to form chain columns, thereby forming a good conductive network and thermal conductive network, so that a polyimide compressed material with a filler chain distribution with excellent nonlinear electrical conductivity and good thermal conductivity can be obtained at a lower filler content.
[0012] Furthermore, the particle sizes of the polyimide molding powder and the pressure-sensitive filler are less than 100 meshes.
[0013] Furthermore, the polyimide molding powder is one or more of YS20 molding powder, A-PI-280 molding powder or cp-8002 molding powder.
[0014] Furthermore, the pressure-sensitive filler is one or more of ZnO, SiC or carbon nanotubes.
[0015] Furthermore, the pressure-sensitive filler and the polyimide molding powder in step S1 are placed in a forced air drying oven at 150-250° C. for 1-3 hours.
[0016] Furthermore, in step S2, the stirring speed is 8000-10000 rpm, the mixing is performed for 5-20 min, and the stirring is stopped and the drum is shaken every 2-3 s.
[0017] The centrifugal force is stronger when stirring at a high speed, which can make the powder mixed more evenly and in a shorter time. However, at the same time, high speed will also cause local overheating, which can easily cause the powder to carbonize. Therefore, stop stirring and shake the drum every 2 to 3 seconds to prevent local overheating and carbonization of the powder.
[0018] Furthermore, in step S3, the sintering temperature is 375-385° C., and the sintering time is 2-2.5 hours.
[0019] Furthermore, in step S4, the AC voltage applied is 60 Hz, so that the molten mixed powder is at 450-500V rms / mm field strength, the AC voltage is applied for 70 to 90 seconds.
[0020] Furthermore, in step S4, the constant pressure pressing is performed at a pressure of 40 to 50 MPa and a time of 30 to 60 min.
[0021] The beneficial effects of the present invention are:
[0022] The present invention utilizes the difference in dielectric constant between the pressure-sensitive filler and the polyimide matrix, and adds an alternating voltage to form an electric field during molten pressing. Under the action of the electric field force, the pressure-sensitive filler is chain-distributed and aggregated to form chain columns, forming a good conductive network and a thermal conductive network, thereby obtaining a polyimide pressed material with a filler chain distribution that has excellent nonlinear electrical conductivity and good thermal conductivity, while minimizing the influence of the filler on the overall performance of the polyimide matrix. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a force analysis diagram of the pressure-sensitive filler particles after voltage is applied in the present invention;
[0024] Figure 2 The flow chart of the preparation of the polyimide compression material with chain distribution of fillers of the present invention;
[0025] Figure 3 The DC breakdown field strength bar graphs of the embodiments of the present invention and the comparative example samples;
[0026] Figure 4 The nonlinear conductivity characteristic diagram of the samples of the embodiment of the present invention and the comparative example;
[0027] Figure 5 The figure is a bar graph of thermal conductivity of the samples of the embodiment of the present invention and the comparative example;
[0028] Figure 6 It is a bar graph of simply supported beam impact strength (unnotched) of samples of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] Embodiment 1:
[0031] like Figure 2 As shown, a method for preparing a polyimide compression material with a filler chain distribution comprises the following steps:
[0032] S1 Raw material pretreatment: Dry a sufficient amount of ZnO pressure-sensitive microsphere filler and fusible YS20 polyimide molding powder at 200°C for 2h, then use a blender to stir and break up the ZnO pressure-sensitive microsphere filler, and pass the ZnO pressure-sensitive microsphere filler and YS20 molding powder through a 100-mesh sieve respectively;
[0033] S2 Mixing and sieving: Use a precision balance to weigh 7.00g of ZnO pressure-sensitive microsphere filler and 63.00g of YS20 molding powder after the treatment in step S1, and use a clean and dry high-speed tissue mixer to mix the ZnO pressure-sensitive microsphere filler and the YS20 molding powder. The mixer speed is set to 10,000 rpm, and the stirring is stopped and the drum is shaken every 2 to 3 seconds. The stirring time is about 10 minutes; when the ZnO pressure-sensitive microsphere filler and the YS20 molding powder are evenly mixed, pour the mixed raw materials into a 150-mesh sieve, pick out the lumps to obtain a mixed powder;
[0034] S3 mold sintering: the sieved mixed powder is spread and evenly loaded into a mold of 101×59×30mm, with a powder laying thickness of 15mm, and then put into a sintering furnace, set the sintering temperature to 375℃, and the sintering time to 2.5h, and sinter the mixed powder to a molten state;
[0035] S4 field pressing: Place the mold containing the molten mixed powder on the hydraulic press platform, apply 60Hz AC voltage from the top and bottom to make the mixture in a field strength of 450Vrms / mm, and apply the electric field for 90 seconds; then press at a constant pressure of 40MPa, and maintain the pressure for 60min to completely shape the mixture; take out the mold and cool it to room temperature for 1h, then demold it to obtain a 101×59×5mm filler chain-distributed 90% YS20+10% ZnO molded material sample.
[0036] Embodiment 2:
[0037] A method for preparing a polyimide compression material with a filler chain distribution comprises the following steps:
[0038] S1 Raw material pretreatment: Dry a sufficient amount of nano-SiC filler and A-PI-280 polyimide molding powder at 200°C for 2h, stir and break up the nano-SiC filler, and pass the nano-SiC filler and A-PI-280 molding powder through a 100-mesh sieve respectively;
[0039] S2: Mixing and sieving: Use a precision balance to weigh 11.00g of the nano-SiC filler and 99.00g of the A-PI-280 molding powder after the treatment in step S1, and use a clean and dry high-speed tissue mixer to mix the nano-SiC filler and the A-PI-280 molding powder. The mixer speed is set to 10,000 rpm, and the stirring is stopped and the drum is shaken every 2 to 3 seconds. The stirring time is about 10 minutes. When the nano-SiC filler and the A-PI-280 molding powder are evenly mixed, pour the mixed raw materials into a 150-mesh sieve, pick out the lumps to obtain a mixed powder;
[0040] S3 mold sintering: the sieved mixed powder is spread and evenly loaded into a mold of 101×59×30mm, with a powder laying thickness of 25mm, and then put into a sintering furnace, and the sintering temperature is set to 385℃, the sintering time is 2h, and the mixed powder is sintered to a molten state;
[0041] S4 field pressing: Place the mold containing the molten mixed powder on the hydraulic press platform, apply a 60Hz AC electric field from the top and bottom to make the mixture in a field strength of 480Vrms / mm, and apply the electric field for 75 seconds; then press at a constant pressure of 50MPa, and maintain the pressure for 40min to allow the mixture to be completely shaped; after taking out the mold and cooling it to room temperature, demolding can be performed to obtain a 101×59×5mm filler chain-distributed 90% A-PI-280+10% SiC molded material sample.
[0042] Comparative Example:
[0043] A method for preparing a polyimide compression material comprises the following steps:
[0044] S1 Raw material pretreatment: Dry a sufficient amount of ZnO pressure-sensitive microsphere filler and YS20 fusible polyimide molding powder at 200°C for 2h, then use a blender to stir and break up the ZnO pressure-sensitive microsphere filler, and pass the ZnO pressure-sensitive microsphere filler and YS20 molding powder through a 100-mesh sieve respectively;
[0045] S2: Mixing and sieving: Use a precision balance to weigh 14.00g of ZnO pressure-sensitive microsphere filler and 56.00g of YS20 molding powder after the treatment in step S1, and use a clean and dry high-speed tissue mixer to mix the ZnO pressure-sensitive microsphere filler and the YS20 molding powder. The mixer speed is set to 10,000 rpm, and the stirring is stopped and the drum is shaken every 2 to 3 seconds. The stirring time is about 10 minutes. When the ZnO pressure-sensitive microsphere filler and the YS20 molding powder are evenly mixed, pour the mixed raw materials into a 150-mesh sieve, pick out the lumps to obtain a mixed powder;
[0046] S3 mold sintering: the sieved mixed powder is spread and evenly loaded into a 101×59×30mm mold with a powder laying thickness of 15mm, and then put into a sintering furnace, set the sintering temperature to 370℃, and the sintering time to 2.5h, and sinter the mixed powder to a molten state;
[0047] S4 Constant pressure pressing: Place the mold filled with molten mixed powder on the hydraulic press platform and press at a constant pressure of 40MPa for 60 minutes to allow the mixture to be completely shaped; after taking out the mold and cooling it to room temperature for 1 hour, you can demold it to obtain a 101×59×5mm 80% YS20+20% ZnO molded material sample with uniformly distributed fillers.
[0048] The 90% YS20 + 10% ZnO pressed sample of Example 1 was machine-processed into a 40×40×2mm small sample and a 80×10×4mm small sample; the 90% A-PI-280 + 10% SiC pressed sample of Example 2 was machine-processed into a 40×40×2mm small sample and a 80×10×4mm small sample; the 80% YS20 + 20% ZnO pressed sample of the comparative example was machine-processed into a 40×40×2mm small sample and a 80×10×4mm small sample; electrical properties, thermal properties and mechanical properties were tested respectively. Among them, the DC breakdown field strength was tested by a laboratory platform, and the test results are shown in Figure 3 As shown; the volume conductivity is tested by the three-electrode method, and the test results are as follows Figure 4 As shown; the thermal conductivity is tested by Hot Disk TPS 3500 thermal conductivity meter, the test results are as follows Figure 5 As shown; the simply supported beam impact strength (without notch) is tested according to the national standard GB / T1043.1-2008. The test results are as follows Figure 6 shown.
[0049] Depend on Figure 3 to Figure 6 Data analysis shows that the 90% YS20+10% ZnO molded material sample with chain-like distribution of fillers in Example 1 is quite close to the 80% YS20+20% ZnO molded material sample prepared normally in the control example in terms of electrical properties such as DC breakdown field strength and nonlinear conductivity characteristics, and the thermal conductivity coefficient is slightly higher than that of the control example, while the simply supported beam breakdown strength (without notch) is increased by 28.9% compared with the control example; this indicates that the preparation method of the present invention can enable the polyimide molded material to form a good conductive network and thermal conductive network at a low filling amount, achieving an effect similar to that of a high filling amount, while effectively reducing the deterioration effect of the high filling amount on the mechanical properties of the material.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyimide compression material with a filler chain distribution, characterized in that: The steps include: S1 raw material pretreatment: drying the pressure-sensitive filler and the polyimide molding powder, stirring and breaking up the pressure-sensitive filler, and then sieving the pressure-sensitive filler and the polyimide molding powder respectively; S2 Mixing and sieving: After the pressure-sensitive filler and the polyimide molding powder are mixed evenly in a mixer, the mixed powder is sieved; S3 mold sintering: the sieved mixed powder is loaded into a mold, and then placed in a sintering furnace to sinter the mixed powder into a molten state; S4 field pressing: apply AC voltage to the upper and lower parts of the mold filled with molten mixed powder, then press and shape at constant pressure, cool to room temperature and demould to obtain a compressed material with chain distribution of fillers.
2. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: The particle sizes of the polyimide molding powder and the pressure-sensitive filler are less than 100 meshes.
3. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: The polyimide molding powder is one or more of YS20 molding powder, A-PI-280 molding powder or cp-8002 molding powder.
4. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: The pressure-sensitive filler is one or more of ZnO, SiC or carbon nanotubes.
5. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: The pressure-sensitive filler and the polyimide molding powder in step S1 are placed in a forced air drying oven at 150-250° C. and dried for 1-3 hours.
6. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: The stirring speed in step S2 is 8000-10000 rpm, and the mixing is performed for 5-20 min. The stirring is stopped and the drum is shaken every 2-3 s.
7. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: The sintering temperature in step S3 is 375-385° C., and the sintering time is 2-2.5 hours.
8. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: In step S4, the AC voltage applied is 60 Hz, so that the molten mixed powder is at 450-500V rms / mm field strength, the AC voltage is applied for 70 to 90 seconds.
9. The method for preparing a polyimide compression material with a filler chain distribution according to claim 1, characterized in that: In the step S4, the constant pressure pressing is performed at a pressure of 40 to 50 MPa and a time of 30 to 60 min.
Citation Information
Patent Citations
Composite material sheet and production method thereof
CN101323173A
Method for preparing zinc oxide / epoxy resin composite voltage dependent resistor
CN104616850A
